Flux architecture : learn to build powerful and scalable applications with Flux, the architecture that serves billions of Facebook users every day /: learn to build powerful and scalable applications with Flux, the architecture that serves billions of Facebook users every day. (2016) - Boduch, Adam
No abstract available